Charge quantity measurement method and charge quantity measurement system
By doping the material into the polarless liquid crystal in the liquid crystal cell and applying a voltage to measure the current to determine the amount of material charge, the problem of insufficient measurement accuracy in the prior art is solved, and the presence of impurity ions in the material is detected with high precision.
Patent Information
- Application Number
- CN202180102707.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-09-27
AI Technical Summary
In the prior art, the accuracy of measuring the charge amount of the material is insufficient, and it is difficult to detect whether the material contains impurity ions with high accuracy.
By incorporating the material to be the measurement object into the non-polar liquid crystal in the liquid crystal cell, a periodically changing voltage is applied, and the current is measured to determine the amount of charge of the material. This method utilizes the high purity and non-rotation characteristics of the polar-invisible liquid crystal to avoid interference caused by impurity ions and achieves high-precision measurement.
The accuracy of measuring the charge amount of the material is improved, and the existence of extremely trace impurity ions in the material can be detected with high accuracy, solving the problem of insufficient accuracy in the prior art.
Smart Images

Figure CN117980751B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a charge amount measurement method and a charge amount measurement system for measuring the charge amount of a material to be measured. Background Art
[0002] Non-patent document 1 discloses a measurement method in which a xylene solution containing green TADF (Thermally Activated Delayed Fluorescence) doped powder is sealed in a test cell, a triangular wave voltage is applied to the test cell, and the current is measured, thereby measuring the amount of impurity ions contained in the TADF doped powder.
[0003] Non-patent document 2 discloses an analysis method of mixing an oligonucleotide DNA (deoxyribonucleic acid) solution and a liquid crystal solution, applying a triangular wave voltage to a liquid crystal cell enclosing the mixed solution, and measuring the current to analyze the physical properties of the oligonucleotide DNA.
[0004] (Prior art literature)
[0005] (Non-patent literature)
[0006] Non-patent literature 1: Inoue M, Oyabu N, Kaneko Y, Kim JY, Yang JH. Correlation between ion impurity in thermally activated delayed fluorescence organic light-emitting diode materials and device lifetime. J. Soc Inf Disp. 2020; 28(11); 905-910.
[0007] Non-patent document 2: Kazuki Iwabata et al 2013 Jpn. J. Appl. Phys. 52 097301 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The techniques disclosed in the above-mentioned non-patent documents 1 and 2 both have the problem that the measurement accuracy of the charge amount of the material to be measured is insufficient.
[0010] Therefore, the present disclosure provides a charge amount measurement method and a charge amount measurement system capable of improving the measurement accuracy of the charge amount of a material to be measured.
[0011] Means for solving problems
[0012] In order to achieve the above-mentioned purpose, a method for measuring the amount of charge involved in one embodiment of the present invention is as follows: in a liquid crystal unit sealed with a sample, a periodically changing voltage is applied between a pair of electrodes sandwiching the sample, the sample is a sample in which a material to be measured is doped into a non-polar liquid crystal, and the non-polar liquid crystal is a liquid crystal in which the liquid crystal molecules do not rotate even when a voltage is applied, and the charge amount of the material to be measured is measured based on the current flowing in the pair of electrodes and the sample due to the application of the voltage.
[0013] In order to achieve the above-mentioned purpose, a method for measuring the amount of charge involved in one embodiment of the present invention is as follows: in a liquid crystal unit in which a sample is sealed in the form of a sample sandwiched by a vertical orientation film, a periodically changing voltage is applied between a pair of electrodes sandwiching the sample and the vertical orientation film, and the sample is a sample in which a material to be measured is doped into a liquid crystal having positive dielectric anisotropy, and the amount of charge on the material to be measured is measured based on the current flowing in the pair of electrodes and the sample due to the application of the voltage.
[0014] In order to achieve the above-mentioned object, a charge quantity measurement system according to one embodiment of the present invention comprises a voltage applying unit and a measuring unit. The voltage applying unit applies a periodically changing voltage between a pair of electrodes sandwiching the sample in a liquid crystal unit sealed with a sample, wherein the sample is a sample in which a material to be measured is doped into a non-polar liquid crystal, and the non-polar liquid crystal is a liquid crystal in which liquid crystal molecules do not rotate even when a voltage is applied. The measuring unit measures the charge quantity of the material to be measured based on the current flowing through the pair of electrodes and the sample due to the application of the voltage.
[0015] Effects of the Invention
[0016] The charge amount measurement method and charge amount measurement system according to the present disclosure have the following advantages, and can improve the measurement accuracy of the charge amount of a material to be measured. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram showing the configuration of a charge amount measurement system according to an embodiment.
[0018] Figure 2 It is a schematic diagram showing a process of manufacturing a liquid crystal cell according to the embodiment.
[0019] Figure 3 It is a schematic diagram showing a liquid crystal cell according to an embodiment.
[0020] Figure 4 This is a diagram showing an example of a line graph plotting voltage (time)-current, which is obtained by measuring a displacement current flowing when a triangular wave voltage is applied to a liquid crystal cell in which polar liquid crystal is sealed.
[0021] Figure 5 This is a diagram showing an example of a line graph plotting voltage (time)-current, which is obtained by measuring a displacement current flowing when a triangular wave voltage is applied to a liquid crystal cell in which a nonpolar liquid crystal is sealed.
[0022] Figure 6 This is a flowchart showing an example of a charge amount measurement method according to the embodiment.
[0023] Figure 7 It is a diagram showing an example of measurement results by the charge amount measurement method according to the embodiment.
[0024] Figure 8 Yes Figure 7 An enlarged view of a portion of an example of a measurement result is shown.
[0025] Fig. 9 This is a diagram showing an example of the measurement results of the ion amount of impurity ions contained in xylene.
[0026] Fig.10 This is a diagram showing an example of the measurement result of the ion amount of impurity ions contained in the nonpolar liquid crystal.
[0027] Fig.11 This is a schematic diagram showing a liquid crystal cell according to a first modification of the embodiment.
[0028] Fig.12 This is a schematic diagram showing a liquid crystal cell according to a second modification of the embodiment. DETAILED DESCRIPTION
[0029] The embodiments will be described in detail below with reference to the drawings.
[0030] In addition, the embodiments to be described below are all general or specific examples. The numerical values, shapes, materials, constituent elements, configuration positions of constituent elements, and connection forms shown in the following embodiments are all examples, and their main purpose is not to limit the technical solution. Moreover, the constituent elements of the following embodiments that are not recorded in the independent technical solution of the highest concept are described as arbitrary constituent elements. Moreover, each figure is not a rigorous illustration. In each figure, the same symbols are given to substantially the same structures, and repeated descriptions are omitted or simplified.
[0031] Figure 1 1 is a schematic diagram showing the configuration of a charge amount measurement system 100 according to the embodiment. Figure 2 1 is a schematic diagram showing a process of manufacturing a liquid crystal cell 3 according to an embodiment. The charge measurement method and charge measurement system 100 according to the embodiment measure the charge amount of the material 5 to be measured. Specifically, the charge measurement method and charge measurement system 100 according to the embodiment measure the charge amount of the material 5 to be measured by applying a voltage to a pair of electrodes 31 of the liquid crystal cell 3 in a liquid crystal cell 3 in which a sample 4 is sealed. The sample 4 is a sample in which the material 5 to be measured is doped into a nonpolar liquid crystal 6.
[0032] like Figure 1 As shown, the charge amount measurement system 100 includes a voltage applying unit 1 and a measuring unit 2 .
[0033] The voltage applying unit 1 is connected between a pair of electrodes 31 (described later) included in the liquid crystal unit 3, and applies a periodically changing voltage between the pair of electrodes 31. In the embodiment, the voltage applying unit 1 is a function generator, which generates a triangular wave voltage as a periodically changing voltage, and applies the generated triangular wave voltage between the pair of electrodes 31. As an example, the frequency of the triangular wave voltage is 0.01 Hz, and the amplitude is ±10 V.
[0034] The frequency and amplitude of the triangular wave voltage are examples and are not limited thereto. However, the frequency of the triangular wave voltage is preferably a relatively low frequency. This is because when the frequency of the triangular wave voltage is high, the polarity of the voltage is affected by the impurity ions 51 (see Fig.11 ) is inverted before reaching the insulating film 32 (described later), so the current caused by the impurity ions 51 moving in the liquid crystal as the measurement object cannot be measured.
[0035] The measuring unit 2 measures the material 5 to be measured based on the current flowing through the pair of electrodes 31 and the sample 4 through the voltage applying unit 1. In the embodiment, the measuring unit 2 includes an IV converter 21 and a voltmeter 22. The IV converter 21 is connected in series with the pair of electrodes 31 of the liquid crystal unit 3, and converts the current flowing through the pair of electrodes 31 and the sample 4 into a voltage. The voltmeter 22 measures the voltage converted by the IV converter 21. In other words, the measuring unit 2 measures the current flowing through the pair of electrodes 31 and the sample 4 by measuring the voltage converted by the IV converter 21 with the voltmeter 22.
[0036] The measuring unit 2 measures the amount of impurity ions 51 contained in the material 5 to be measured by measuring the current (displacement current) flowing through the pair of electrodes 31 and the sample 4 . Details will be described later.
[0037] Figure 3 is a schematic diagram showing a liquid crystal unit 3 according to an embodiment. Figure 3 As shown, the liquid crystal cell 3 is composed of a pair of glass substrates 30, a pair of electrodes 31, a pair of insulating films 32, and a sealant 33. In the embodiment, the liquid crystal cell 3 is in the shape of a square with a side length of several centimeters in a plan view. Figure 3 2 shows a state where the sample 4 is sealed in the liquid crystal cell 3 .
[0038] A pair of electrodes 31 are both ITO (Indium Tin Oxide) electrodes, and are transparent electrodes. In addition, the material constituting the pair of electrodes 31 is not particularly limited. For example, the pair of electrodes 31 may both be Al (aluminum) electrodes. The electrode 31 on one side (here, the upper side) of the pair of electrodes 31 is formed on a surface (here, the lower surface) of the glass substrate 30 on one side (here, the upper side) of the pair of glass substrates 30. Furthermore, the electrode 31 on the other side (here, the lower side) of the pair of electrodes 31 is formed on a surface (here, the upper surface) of the glass substrate 30 on the other side (here, the lower side) of the pair of glass substrates 30.
[0039] The pair of insulating films 32 are both SiN (Silicon nitride) insulating films. In addition, the material constituting the pair of insulating films 32 is not particularly limited. For example, the pair of insulating films 32 may both be polyimide insulating films. The insulating film 32 of one side (here, the upper side) of the pair of insulating films 32 is formed on a surface (here, the lower surface) of the electrode 31 of one side (here, the upper side) of the pair of electrodes 31. In addition, the insulating film 32 of the other side (here, the lower side) of the pair of insulating films 32 is formed on a surface (here, the upper surface) of the electrode 31 of the other side (here, the lower side) of the pair of electrodes 31. The pair of insulating films 32 are configured to face each other with the space Sp1 for enclosing the sample 4 sandwiched therebetween. Therefore, the pair of glass substrates 30 and the pair of electrodes 31 are also configured to face each other with the above-mentioned space Sp1 sandwiched therebetween.
[0040] The sealant 33 is applied between the pair of glass substrates 30, the pair of electrodes 31, and the pair of insulating films 32 so as to cover the space Sp1. In other words, the space Sp1 is formed by the pair of glass substrates 30, the pair of electrodes 31, the pair of insulating films 32, and the sealant 33. In addition, since a portion of each of the pair of electrodes 31 is exposed to the outside, the voltage applying unit 1 and the measuring unit 2 can be electrically connected to the exposed portion via an electric wire.
[0041] The material 5 to be measured is an organic material such as P3HT (Poly (3-hexylthiophene): polytrihexylthiophene) used as a material for an organic solar cell, or a material used in an HTL (Hole Transport Layer) of organic electroluminescence. In an embodiment, the material 5 to be measured is a material for an HTL of organic electroluminescence. In addition, the material 5 to be measured may be an organic material such as DNA, or an inorganic material. In an embodiment, the material 5 to be measured that is doped into the nonpolar liquid crystal 6 is a particle, a powder, or a liquid. In addition, the liquid referred to here may include not only a solution in which the material 5 to be measured is dissolved, but also the material 5 itself, in which the solvent is the measured object.
[0042] The nonpolar liquid crystal 6 is a liquid crystal whose liquid crystal molecules do not rotate even when voltage is applied. In other words, the nonpolar liquid crystal 6 can also be called a neutral liquid crystal. Furthermore, the nonpolar liquid crystal 6 is a liquid crystal whose dielectric anisotropy Δε is zero or almost zero. The dielectric anisotropy Δε is represented by the difference between the dielectric constant in the axial direction of the liquid crystal molecules and the dielectric constant in the direction orthogonal to the axial direction of the liquid crystal molecules. In an embodiment, the nonpolar liquid crystal 6 is a fluorine-containing nematic liquid crystal (Nematic Liquid Crystal). More specifically, in an embodiment, the nonpolar liquid crystal 6 is, for example, a liquid crystal with a model name of NA-1345 produced by DIC Corporation. Of course, the nonpolar liquid crystal 6 is not limited to the liquid crystals of the above-mentioned products.
[0043] Here, the difference in characteristics between the nonpolar liquid crystal 6 and the polar liquid crystal is described using Figure 4 as well as Figure 5 The polar liquid crystal mentioned here refers to liquid crystal in which the liquid crystal molecules rotate when a voltage is applied. In other words, the polar liquid crystal is a liquid crystal with a positive dielectric anisotropy Δε or a liquid crystal with a negative dielectric anisotropy Δε.
[0044] Figure 4 This is a diagram showing an example of a line graph (VI curve) plotting voltage V (time)-current I, which is obtained by measuring a displacement current flowing when a triangular wave voltage is applied to a liquid crystal cell enclosing polar liquid crystals. Figure 5 This is a diagram showing an example of a line graph (VI curve) depicting voltage V (time)-current I, which is obtained by measuring the displacement current flowing when a triangular wave voltage is applied to a liquid crystal cell sealed with non-polar liquid crystal 6. Here, only liquid crystal is sealed in the liquid crystal cell, and the material 5 to be measured is not mixed in the liquid crystal.
[0045] exist Figure 4 In , the reciprocal of the tilt A1 relative to the V axis represents the resistance value of the polar liquid crystal. Figure 4 In FIG. 1 , the length A2 of the I axis of the parallelogram-shaped line graph represents the capacitance of the polar liquid crystal. Figure 4 In FIG. 1 , the peak value A3 on the I axis of the parallelogram-shaped line graph represents the switching voltage (in other words, the switching current) of the polar liquid crystal. Figure 4 In FIG. 1 , the area of the convex portion A4 protruding from the parallelogram-shaped line graph represents the density of the impurity ions 51 contained in the polar liquid crystal. Figure 4 In FIG. 1 , the horizontal width A5 of the V-axis direction of the parallelogram-shaped line graph represents the mobility of the impurity ions 51 contained in the polar liquid crystal. The peak A3, the convex portion A4, and the horizontal width A5 appear not only in the first quadrant but also in the third quadrant.
[0046] like Figure 4 As shown, when polar liquid crystal is used as a solvent in a liquid crystal cell, the switching current (peak value A3) of the polar liquid crystal appears in the measurement result of the displacement current, and the physical properties (convex portion A4 and horizontal width A5) of the impurity ions 51 contained in the polar liquid crystal appear in the measurement result of the displacement current. Therefore, when a sample in which the material 5 to be measured is doped into the polar liquid crystal and sealed in the liquid crystal cell, not only the physical properties of the material 5 to be measured but also the physical properties of the polar liquid crystal appear in the measurement result of the displacement current.
[0047] exist Figure 5 In , the reciprocal of the inclination relative to the V axis represents the resistance value R of the nonpolar liquid crystal 6. Figure 5 In FIG. 1 , the upper side of the parallelogram-shaped line graph represents the current Ip flowing in the liquid crystal cell when the voltage applied to the liquid crystal cell increases, and the lower side of the parallelogram-shaped line graph represents the current In flowing in the liquid crystal cell when the voltage applied to the liquid crystal cell decreases. Figure 5 In FIG. 1 , the longitudinal length of the parallelogram-shaped line graph in the I-axis direction is the difference ΔI between the current Ip and the current In described above, which represents the capacitance of the nonpolar liquid crystal 6 .
[0048] like Figure 5 As shown, when nonpolar liquid crystal 6 is used as a solvent in a liquid crystal cell, since the liquid crystal molecules do not rotate due to the application of voltage, the switching current does not appear in the measurement result of the displacement current as in the case of polar liquid crystal. In addition, in this case, the nonpolar liquid crystal 6 has a higher purity than the polar liquid crystal, and therefore contains almost no impurity ions 51, and the physical properties of the impurity ions 51 do not appear in the measurement result of the displacement current, or even if they do appear, they are very small. Therefore, in the case of a sample obtained by doping the material 5 to be measured with the nonpolar liquid crystal 6 sealed in the liquid crystal cell, only the physical properties of the material 5 to be measured will appear in the measurement result of the displacement current.
[0049] The following method for making the liquid crystal unit 3 utilizes Figure 2 as well as Figure 3 To illustrate. First, prepare a nonpolar liquid crystal 6 and a material 5 to be measured, and mix the material 5 to be measured into the nonpolar liquid crystal 6 to produce a sample 4. Next, prepare a liquid crystal cell 3, in which the space Sp1 is empty, and seal the produced sample 4 into the liquid crystal cell 3. Here, two injection holes 34 are formed in the area where the sealant 33 is applied in the liquid crystal cell 3. The produced sample 4 is sealed into the liquid crystal cell 3 from at least one of the two injection holes 34 by using a capillary phenomenon. Through the above steps, the liquid crystal cell 3 in which the sample 4 is sealed can be produced.
[0050] <Method>
[0051] The following use Figure 6 The operation of the charge amount measurement system 100 according to the embodiment, that is, a charge amount measurement method will be described. Figure 6 FIG. 1 is a flowchart showing an example of a charge amount measurement method according to an embodiment of the present invention. Figure 6 The above-mentioned process of manufacturing the liquid crystal unit 3 is also included.
[0052] First, the material 5 to be measured is doped into the nonpolar liquid crystal 6 to prepare the sample 4 (step S1). Next, the prepared sample 4 is sealed in the liquid crystal cell 3 whose space Sp1 is empty to prepare the liquid crystal cell 3 sealed with the sample 4 (step S2).
[0053] Next, the liquid crystal cell 3 is heated (step S3). Here, the liquid crystal cell 3 is heated until the ambient temperature of the liquid crystal cell 3 reaches about 60 degrees Celsius. Then, while the liquid crystal cell 3 is heated or the liquid crystal cell 3 is in a high temperature environment, the voltage applying unit 1 applies a voltage (here, a triangular wave voltage) between a pair of electrodes 31 of the liquid crystal cell 3 (step S4). In other words, in the embodiment, step S4 of applying a voltage between a pair of electrodes 31 can be performed at a temperature higher than normal temperature (here, about 60 degrees Celsius).
[0054] By heating the liquid crystal unit 3 in this way, the viscosity of the nonpolar liquid crystal 6 can be reduced, and the charge of the material 5 to be measured in the nonpolar liquid crystal 6 or the mobility of the impurity ions 51 contained in the material 5 to be measured can be increased. Specifically, the mobility of the ions is expressed by the following mathematical formula. In the following mathematical formula, "μ" represents the mobility of the ions, "Z" represents the valence of the ions, "e" represents the basic charge, "η" represents the viscosity of the liquid crystal, and "γ" represents the viscosity of the liquid crystal. s ” represents the Stokes radius of the ion.
[0055] [Mathematical formula 1]
[0056]
[0057] As shown in the above mathematical formula, the smaller the viscosity "η" of the liquid crystal is, the greater the mobility of the ions, that is, the mobility of the impurity ions 51. Accordingly, in step S5 of measuring the charge amount of the material 5 to be measured, the measurement accuracy of the charge amount of the material 5 to be measured or the impurity ions 51 contained in the material 5 to be measured can be further improved compared to the case where the liquid crystal cell 3 is not heated.
[0058] Next, the measuring unit 2 measures the current (displacement current) flowing through the pair of electrodes 31 of the liquid crystal cell 3 and the sample 4, and measures the charge amount of the material 5 to be measured based on the measured current (step S5).
[0059] Here we use Figure 7 as well as Figure 8 A specific example of measuring the charge amount of the material 5 to be measured will be described. Figure 7 It is a diagram showing an example of measurement results by the charge amount measurement method according to the embodiment. Figure 8 Yes Figure 7 An enlarged view of a portion of an example of a measurement result is shown. Figure 7 as well as Figure 8 In the measurement results shown, the vertical axis represents the current (unit is “pA”) flowing through the pair of electrodes 31 and the sample 4 , and the horizontal axis represents the voltage (unit is “V”) applied between the pair of electrodes 31 .
[0060] exist Figure 7 as well as Figure 8 The solid line in FIG. 1 represents the measurement result of the following liquid crystal cell 3, in which a sample 4 prepared by doping a material 5 to be measured into a nonpolar liquid crystal 6 is sealed. Figure 7 as well as Figure 8 The dotted line in represents the measurement result of the liquid crystal cell 3 in which only the nonpolar liquid crystal 6 is sealed. Figure 7 as well as Figure 8 The dotted line in the figure shows the measurement result of the liquid crystal cell 3 in which a sample prepared by doping the material 5 to be measured, from which impurities have been removed by sublimation purification, into the nonpolar liquid crystal 6 is sealed. In any sample, the concentration of the material 5 to be measured is 1 wt%.
[0061] like Figure 7 as well as Figure 8 As shown by the dotted line in FIG. 1 , in the measurement results of the liquid crystal cell 3 in which only the nonpolar liquid crystal 6 is sealed, no peak protruding from the parallelogram-shaped line graph is generated. Figure 7 as well as Figure 8 As shown by the solid line in FIG, when the material 5 to be measured contains impurities (including impurity ions 51), a peak protruding from the parallelogram-shaped line graph is generated. In other words, by calculating the area including this peak ( Figure 7 By measuring the area of the shaded area in the figure, it is possible to measure the charge amount of the impurity ions 51 contained in the material 5 to be measured, in other words, the ion amount of the impurity ions 51 can be measured.
[0062] Furthermore, Figure 8As shown by the dotted line in FIG. 1 , it can be seen that in the measurement result when the material 5 to be measured is subjected to sublimation purification, a peak protruding from the parallelogram-shaped line graph is also generated. Thus, by calculating the area including this peak ( Figure 8 By measuring the area of the shaded area in the figure, it is possible to measure the charge amount of the impurity ions 51 that still remain slightly in the material 5 to be measured even when the impurities have been removed by sublimation purification. In other words, it is possible to measure the ion amount of the impurity ions 51.
[0063] <Advantages>
[0064] Advantages of the charge amount measurement method and charge amount measurement system 100 according to the embodiment will be described below. First, the background of the technology for measuring the charge amount of the material 5 to be measured as in the charge amount measurement method and charge amount measurement system 100 according to the embodiment will be described.
[0065] For example, when an organic material or an inorganic material contains impurity ions 51, the impurity ions 51 may adversely affect the characteristics of a device (such as a solar cell) using the organic material or the inorganic material. Therefore, when manufacturing a device, it is important to measure whether the organic material or the inorganic material used to manufacture the device contains impurity ions 51.
[0066] Here, as a method for analyzing the material 5 to be measured, scientific analysis methods such as HPLC (High Performance Liquid Chromatography) are known. However, it is difficult to detect whether the material 5 to be measured contains impurity ions 51 using HPLC.
[0067] In this regard, a method of detecting whether the material 5 to be measured contains impurity ions 51 by an electrical analysis method that measures the charge amount of the material 5 to be measured is known, and this method has been disclosed in, for example, Non-Patent Documents 1 and 2.
[0068] As described in the background art, the following measurement method is disclosed in non-patent document 1, wherein a xylene solution containing green TADF-doped powder is sealed in a test cell, a triangular wave voltage is applied to the test cell, and the current is measured, thereby measuring the amount of impurity ions contained in the TADF-doped powder. However, a problem existing in the technology disclosed in non-patent document 1 is that the impurity ions contained in the xylene solution itself may affect the measurement. This is described in detail below.
[0069] Fig. 9FIG. 1 is a diagram showing an example of the measurement result of the ion amount of impurity ions contained in xylene. Fig. 9 The vertical axis represents the amount of impurity ions, and the horizontal axis represents time. Here, the amount of impurity ions is represented by the sum of the charges of the impurity ions. Fig. 9 As shown, the amount of impurity ions contained in xylene changes with the passage of time, and the amount of ions is relatively large, for example, several pC to several tens of pC.
[0070] Therefore, even if one wants to measure the charge amount of the material 5 to be measured using the technology disclosed in Non-Patent Document 1, it is difficult to measure the charge amount of the material 5 to be measured with high accuracy because the measurement result includes the ion amount of impurity ions contained in xylene. In addition, the ion amount of impurity ions contained in xylene changes with the passage of time, so it is difficult to apply a method in which only the ion amount of impurity ions of xylene is measured in advance and then the difference between the measurement result and the charge amount of the material 5 to be measured is calculated.
[0071] In this regard, the inventors of the present invention have discovered the following solution: when the material 5 to be measured is added to the non-polar liquid crystal 6, the non-polar liquid crystal 6 is a high-purity liquid crystal and the measurement result does not include the switching current. Therefore, it is possible to measure only the charge amount of the impurity ions 51 contained in the material 5 to be measured. In other words, it is possible to detect with high precision whether the material 5 to be measured contains impurity ions 51.
[0072] Fig.10 1 is a diagram showing an example of the measurement result of the ion amount of impurity ions contained in the nonpolar liquid crystal 6. The measurement result is the result of measurement at a temperature higher than room temperature (here, about 60 degrees Celsius). Fig.10 The vertical axis represents the amount of impurity ions, and the horizontal axis represents time. Here, the amount of impurity ions is represented by the sum of the charges of the impurity ions. Fig.10 As shown, the impurity ions in the nonpolar liquid crystal are almost non-existent, that is, close to zero, and even if there are very small amounts of impurity ions, the amount of the ions hardly changes over time. That is, the nonpolar liquid crystal 6 has a purity such that the change in the charge amount of the nonpolar liquid crystal 6 (here, the amount of impurity ions contained in the nonpolar liquid crystal 6) over time is less than 0.1 pC.
[0073] Therefore, in the charge amount measurement method and charge amount measurement system 100 according to the embodiment, the charge amount of the material 5 to be measured (here, the ion amount of the impurity ions 51 contained in the material 5 to be measured) can be measured with high accuracy compared to the case where xylene is used as a solvent to be doped into the material 5 to be measured. Specifically, in the charge amount measurement method and charge amount measurement system 100 according to the embodiment, it is possible to measure an extremely small amount (for example, a few pC) of the impurity ions 51 contained in the material 5 to be measured.
[0074] As described in the background art, the following analysis method is disclosed in non-patent document 2, wherein an oligonucleotide DNA solution is mixed with a liquid crystal solution, and a triangular wave voltage is applied to a liquid crystal unit enclosed with the mixed solution and the current is measured, thereby analyzing the physical properties of the oligonucleotide DNA. More specifically, in non-patent document 2, a sample is prepared by doping oligonucleotide DNA into a liquid crystal having a negative dielectric anisotropy Δε, and the sample is enclosed in a liquid crystal unit having a horizontal alignment film. In other words, in non-patent document 2, the rotation of the liquid crystal molecules caused by the application of voltage is restricted by a horizontal alignment film, thereby suppressing the switching current.
[0075] Although the charge amount of oligonucleotide DNA can be measured in the technology disclosed in non-patent document 2, the charge amount measured is several hundred pC due to the relatively low purity of liquid crystal, so it is difficult to achieve a measurement accuracy of several pC. Therefore, in the technology disclosed in non-patent document 2, it is difficult to detect with high accuracy whether the material 5 to be measured contains impurity ions 51. In contrast, the charge amount measurement method and charge amount measurement system 100 involved in the embodiment can detect with high accuracy whether the material 5 to be measured contains impurity ions 51 as described above.
[0076] In addition, the non-patent document 2 also has the problem that it is difficult to measure the charge amount of the oligonucleotide DNA if the oligonucleotide DNA is not amplified in the preparation stage of the measurement. On the other hand, in the charge amount measurement method and charge amount measurement system 100 disclosed in the present invention, when the material 5 to be measured is DNA, the charge amount of the DNA can be measured without amplifying the DNA in the preparation stage of the measurement.
[0077] As described above, the charge amount measurement method and charge amount measurement system 100 according to the embodiment have the advantage of being able to improve the measurement accuracy of the charge amount of the material 5 to be measured, compared with the techniques disclosed in Non-Patent Documents 1 and 2.
[0078] (Variation Example)
[0079] The above is an explanation of the charge measurement method and charge measurement system involved in the present disclosure based on the implementation mode, but the present disclosure is not limited to the implementation mode. Within the scope of the main purpose of the present disclosure, various forms obtained by performing various modifications that can be thought of by those skilled in the art on the implementation mode, or other forms constructed by combining some of the constituent elements in the implementation mode are also included in the scope of the present disclosure.
[0080] In the above embodiment, step S4 of applying a voltage between the pair of electrodes 31 of the liquid crystal cell 3 is performed at a temperature higher than room temperature, but the present invention is not limited thereto. For example, step S4 may be performed at room temperature.
[0081] In the above embodiment, the sample 4 formed by doping the material 5 to be measured into the nonpolar liquid crystal 6 is sealed in the liquid crystal cell 3, but the present invention is not limited to this. Fig.11 as well as Fig.12 To explain.
[0082] Fig.11 1 is a schematic diagram showing a liquid crystal unit 3A according to a first variant of the embodiment. Fig.11 As shown, a sample 4A in which a material 5 to be measured is doped into a liquid crystal 6A having a positive dielectric anisotropy Δε is sealed in a liquid crystal cell 3A. In addition, a pair of vertical alignment films 35 are formed in the liquid crystal cell 3A instead of a pair of insulating films 32. Therefore, in the liquid crystal cell 3A, the pair of vertical alignment films 35 restricts the rotation of liquid crystal molecules in the liquid crystal 6A caused by the application of voltage, thereby suppressing the switching current.
[0083] In the first modification, if the purity of the liquid crystal 6A can be made close to that of the nonpolar liquid crystal 6 , the measurement accuracy of the charge amount of the material 5 to be measured can be improved similarly to the case of the nonpolar liquid crystal 6 .
[0084] Fig.12 2 is a schematic diagram showing a liquid crystal unit 3B according to a second variant of the embodiment. Fig.12 As shown, a sample 4B in which a material 5 to be measured is doped into a liquid crystal 6B having a negative dielectric anisotropy Δε is sealed in a liquid crystal cell 3B. In addition, a pair of horizontal alignment films 36 are formed in the liquid crystal cell 3B instead of a pair of insulating films 32. Therefore, in the liquid crystal cell 3B, the pair of horizontal alignment films 36 restricts the rotation of liquid crystal molecules in the liquid crystal 6B caused by the application of voltage, thereby suppressing the switching current.
[0085] In the second variant, as in the first variant, if the purity of liquid crystal 6B can be made close to that of nonpolar liquid crystal 6, the measurement accuracy of the charge amount of material 5 to be measured can be improved as in the case of nonpolar liquid crystal 6.
[0086] In the above-mentioned embodiment, the charge amount measurement method and the charge amount measurement system 100 measure the ion amount of the impurity ions 51 contained in the material 5 to be measured, but the present invention is not limited to this. As described above, for example, when the material 5 to be measured is DNA, the charge amount measurement method and the charge amount measurement system 100 measure the charge amount of DNA. In other words, the charge amount measurement method and the charge amount measurement system 100 can be used to measure the charge amount of the material 5 itself to be measured, and can also be used to measure the charge amount of impurities contained in the material 5 to be measured.
[0087] (Summarize)
[0088] As described above, the charge measurement method involved in the present disclosure is as follows: in a liquid crystal unit 3 enclosed with a sample 4, a periodically changing voltage is applied between a pair of electrodes 31 sandwiching the sample 4 (step S4); the sample 4 is a sample in which a material 5 to be measured is doped into a non-polar liquid crystal 6; the non-polar liquid crystal 6 is a liquid crystal in which the liquid crystal molecules do not rotate even when a voltage is applied; based on the current flowing in the pair of electrodes 31 and the sample 4 due to the application of the voltage, the charge of the material 5 to be measured is measured (step S5).
[0089] According to this, since there is almost no displacement current caused by the nonpolar liquid crystal 6, it is possible to measure the charge amount caused only by the material 5 to be measured. In other words, as described above, there is an advantage that the measurement accuracy of the charge amount of the material 5 to be measured can be improved compared to the case of using a solvent other than the nonpolar liquid crystal 6.
[0090] Furthermore, in the charge amount measurement method according to the present disclosure, the nonpolar liquid crystal 6 has a purity such that a change in the charge amount of the nonpolar liquid crystal 6 over time is 0.1 pC or less.
[0091] This allows the amount of charge resulting only from the material 5 to be measured to be measured with higher accuracy, thus providing an advantage in that the accuracy of measurement of the amount of charge of the material 5 to be measured can be further improved.
[0092] In addition, the charge amount measurement method involved in the present disclosure is as follows: in a liquid crystal unit 3A in which a sample 4A is sealed in the form of a sample 4A sandwiched by a vertical orientation film 35, a periodically changing voltage is applied between a pair of electrodes 31 sandwiching the sample 4A and the vertical orientation film 35 (step S4), and the sample 4A is a sample in which a material 5 to be measured is doped into a liquid crystal 6A having a positive dielectric anisotropy, and the charge amount of the material 5 to be measured is measured based on the current flowing in the pair of electrodes 31 and the sample 4A due to the application of the voltage (step S5).
[0093] According to this, since there is almost no displacement current caused by the liquid crystal 6A, it is possible to measure the charge amount caused only by the material 5 to be measured. In other words, as described above, there is an advantage that the measurement accuracy of the charge amount of the material 5 to be measured can be improved compared to the case of using a solvent other than the nonpolar liquid crystal 6 and the liquid crystal 6A.
[0094] Furthermore, in the charge amount measurement method according to the present disclosure, step S4 of applying a voltage between the pair of electrodes 31 is performed at a temperature higher than room temperature (step S3 ).
[0095] Accordingly, the viscosity of the liquid crystal serving as the solvent for the sample 4 can be reduced, thereby increasing the charge of the material 5 to be measured that exists in the liquid crystal or the mobility of the impurity ions 51 contained in the material 5 to be measured. This results in the advantage of being able to further improve the measurement accuracy of the charge amount of the material 5 to be measured.
[0096] Furthermore, in the charge amount measurement method according to the present disclosure, step S5 of measuring the charge amount of the material 5 to be measured is a step of measuring the ion amount of the impurity ions 51 included in the material 5 to be measured.
[0097] According to this, since there is almost no displacement current caused by the liquid crystal 6A, it is possible to measure the charge amount caused only by the impurity ions 51 contained in the material 5 to be measured. In other words, as described above, there is an advantage that the measurement accuracy of the ion amount of the impurity ions 51 contained in the material 5 to be measured can be improved compared to the case of using a solvent other than the nonpolar liquid crystal 6 and the liquid crystal 6A.
[0098] In addition, the charge quantity measurement system 100 involved in the present disclosure includes a voltage application unit 1 and a measurement unit 2. The voltage application unit 1 applies a periodically changing voltage between a pair of electrodes 31 sandwiching the sample 4 in the liquid crystal cell 3 in which the sample 4 is sealed. The sample 4 is a sample in which a material 5 to be measured is mixed into a non-polar liquid crystal 6. The non-polar liquid crystal 6 is a liquid crystal in which the liquid crystal molecules do not rotate even when a voltage is applied. The measurement unit 2 measures the charge quantity of the material 5 to be measured based on the current flowing through the pair of electrodes 31 and the sample 4 due to the application of the voltage.
[0099] According to this, since there is almost no displacement current caused by the nonpolar liquid crystal 6, it is possible to measure the charge amount caused only by the material 5 to be measured. In other words, as described above, there is an advantage that the measurement accuracy of the charge amount of the material 5 to be measured can be improved compared to the case of using a solvent other than the nonpolar liquid crystal 6.
[0100] Industrial Applicability
[0101] The present disclosure can be applied to, for example, a method and a system for measuring the amount of electric charge on a material to be measured.
[0102] Explanation of symbols
[0103] 1 Voltage application unit
[0104] 2 Measurement Department
[0105] 21I-V Converter
[0106] 22Voltmeter
[0107] 3, 3A, 3B liquid crystal unit
[0108] 30 Glass substrate
[0109] 31 Electrode
[0110] 32 Insulation film
[0111] 33 Sealant
[0112] 34 Injection port
[0113] 35 Vertically oriented film
[0114] 36 Horizontal orientation film
[0115] 4, 4A, 4B samples
[0116] 5 Materials to be measured
[0117] 51 Impurity ions
[0118] 6 Non-polar liquid crystal
[0119] 6A Liquid crystal with positive dielectric anisotropy
[0120] 6B Liquid crystal with negative dielectric anisotropy
Claims
1. A method for measuring a charge amount, wherein: In a liquid crystal unit sealed with a sample, a periodically changing voltage is applied between a pair of electrodes sandwiching the sample. The sample is a sample in which a material to be measured is mixed into a nonpolar liquid crystal, and the nonpolar liquid crystal is a liquid crystal in which the liquid crystal molecules do not rotate even when a voltage is applied. The amount of charge on the material to be measured, that is, the amount of impurity ions contained in the material to be measured, is measured based on the current flowing through the pair of electrodes and the sample due to the application of the voltage.
2. The charge quantity measuring method according to claim 1, The nonpolar liquid crystal has a purity such that a change in the amount of charge of the nonpolar liquid crystal over time is less than 0.1 pC.
3. The charge quantity measuring method according to claim 1 or 2, The step of applying a voltage between the pair of electrodes is performed at a temperature higher than normal temperature.
4. A charge measurement system comprising: a voltage applying unit for applying a periodically changing voltage between a pair of electrodes sandwiching a sample in a liquid crystal cell sealed therein, wherein the sample is a sample in which a material to be measured is doped into a nonpolar liquid crystal, wherein the liquid crystal molecules do not rotate even when a voltage is applied; and The measuring unit measures the charge amount of the material to be measured, that is, the ion amount of impurity ions contained in the material to be measured, based on the current flowing through the pair of electrodes and the sample due to the application of the voltage.
Citation Information
Patent Citations
Test method for ion density in liquid crystal material
CN109031732A